Edukasi Hipertensi dan Pengukuran Tekanan Darah pada Komunitas Ibu-Ibu Pengajian - Milla, Izatul; Rahmawati, Lailatul (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
Hypertension is a global health problem that contributes significantly to increased morbidity and mortality rates due to cardiovascular disease. Dietary factors, such as high consumption of salt, saturated fat, and processed foods, are the main causes of increased risk of hypertension in the community. This community service activity aimed to increase knowledge, awareness, and preventive behavior regarding hypertension through counseling and blood pressure checks for mothers who play an important role in determining their families' dietary patterns. The activity methods included interactive lectures, question and answer sessions, blood pressure checks, and pre-test and post-test evaluations of 40 participants. The results of the activity showed an average increase in knowledge of 30.1% after the counseling, with 60% of participants having normal blood pressure and 15% showing mild hypertension. In addition to increased knowledge, there was a positive change in attitude, with more than 80% of participants committing to improving their diet and conducting regular blood pressure checks. This activity proved effective in improving health literacy and awareness of hypertension prevention at the household level. In the long term, this activity is expected to create a community of mothers who are aware of hypertension and act as agents of change in creating healthy families.